PENGARUH KOMPOSISI NANO SEMEN PADA PERILAKU BETON - Elfiranahla Chandra Dewi; Kartika Trisna Apsari; Purwanto Purwanto; Han Ay Lie (Jurnal Karya Teknik Sipil, 2013)
This study aimed to investigate the influence of the composition nano-cement to compressive strength and flexural strength on concrete. First step in the produced of concrete with nano materials, necessary constituent concepts concrete material selection right. Cement with fine grains have a larger surface area than the coarse grained cement, thus increasing the surface area of a grain of cement hydration process faster so that more amount of cement that can react with water to increase  so the compressive strength will be increase too. Increased in the compressive strength of concrete will be accompanied by a increased in flexural strength. To determine the effect of the composition nano-cement was used variation of composition nano-cement 0%, 5%, 10%, 15%, and 20%. Specimens for compression test is a cylindrical 10 cm diameter and 20 cm high, and Specimens for flexural test is  15 x 15 x 60 cm. The tools used in the testing is a load cell, LVDT (Linear Variable Displacement Transducer), and data loggers. Through this research is expected, in addition to knowing its effects on concrete compressive strength and flexural strength, can also determine relationship between compressive strength and flexural strength.